Criança psicótica brinca?: considerações acerca do brincar na psicose - Julia Maciel Soares (Estilos da Clínica, 2008)
This paper discusses the playing as a symbolic activity, which is defined as the representation of what is absent. Therefore, to take place, it depends on the separation process. It discusses the playing of psychotic children, for whom the subjective position was structured without the absence inscription. Through the study of two short clinical cases, it examines whether the ludic activity of a psychotic child is, indeed, a playing activity.